Masters and students: Jesuit Mission ethnography in seventeenth-century New France - True, Micah (McGill-Queen's Univ. Press, 2015)
Introduction : Jesuit mission ethnography -- Amerindian languages and the beginning of the Jesuit mission to New France -- Very rich and very poor : Jesuit missionary linguistics in New France -- Religious conversion and Amerindian cruelty in the Jesuit Relations -- Messou the great restorer : questioning Montagnais religious knowledge -- Travelling texts : toward a decentred reading of Jesuit mission ethnography -- The end(s) of Jesuit mission ethnography